The effectiveness of spatially cross-linked polymer in the postoperative epidural fibrosis prevention: an experimental study - K. Ts. Erdyneev; V. A. Sorokovikov; D. N. Sambuev; V. P. Saganov; B. B. Dambaev; S. N. Larionov; O. A. Goldberg; S. A. Lepekhova; I. A. Stepanov (Acta Biomedica Scientifica, 2021)
Introduction. Epidural fibrosis is an urgent problem in modern spinal surgery and orthopedics. The formation of connective tissue in the epidural space after performing surgical interventions on the spinal column inevitably leads to adhesion of the latter to the dura mater and compression of neural structures, followed by the formation of clinical and neurological symptoms. The  search for literary sources in domestic and foreign scientific databases has demonstrated the presence of several works studying the effectiveness of barrier methods for preventing the development of epidural fibrosis. It should be noted that the results of these studies are ambiguous and largely contradictory.The purpose was to study the effectiveness of using a spatially cross-linked polymer in the postoperative lumbar epidural fibrosis prevention in an experiment.Materials and methods. The study included 26 male Wistar rats (average body weight 338.5±9.07 g), which were divided into two groups: Group I (control, n = 12): animals underwent laminectomy at the level of vertebral bodies LVII – SI  without application of spatially crosslinked polymer; Group II (experimental, n = 14): animals underwent laminectomy at the level of vertebral bodies LVII – SI  followed by application of a spatially cross-linked polymer to the dura mater. The morphological and instrumental parameters were studied.Results. Significant differences were noted in the severity of epidural fibrosis (χ2 = 14.846, p = 0.003), the number of newly formed vessels (F = 14.371, p<0.001), the number of fibroblasts (F = 11.158, p<0.001), as well as in the severity of vertebral stenosis channe l according to multislice computed tomography (χ2 = 17.207, p=0.002) between the control and experimental groups of animals.Conclusion. Application of a spatially cross-linked polymer to the dura mater is an effective way to prevent the development of postoperative epidural fibrosis.